Ocean acidification and the Permo-Triassic mass extinction - Clarkson, MO; Kasemann, SA; Wood, RA; Lenton, TM; Daines, SJ; Richoz, S; Ohnemueller, F; Meixner, A; Poulton, SW; Tipper, ET (Science, 2015)
This is the author accepted manuscript. The final version is available from the publisher via the DOI in this record. Ocean acidification triggered by Siberian Trap volcanism was a possible kill mechanism for the Permo-Triassic Boundary mass extinction, but direct evidence for an acidification event is lacking. We present a high-resolution seawater pH record across this interval, using boron isotope data combined with a quantitative modeling approach. In the latest Permian, increased ocean alkalinity primed the Earth system with a low level of atmospheric CO2 and a high ocean buffering capacity. The first phase of extinction was coincident with a slow injection of carbon into the atmosphere, and ocean pH remained stable. During the second extinction pulse, however, a rapid and large injection of carbon caused an abrupt acidification event that drove the preferential loss of heavily calcified marine biota. M.O.C. acknowledges funding from the Edinburgh University Principal’s Career Development Scholarship, the International Centre for Carbonate Reservoirs, and The Marsden Fund (U001314). R.A.W., T.M.L., and S.W.P. acknowledge support from the Natural Environment Research Council through the “Co-evolution of Life and the Planet” scheme (NE/I005978). T.M.L. and S.J.D. were supported by the Leverhulme Trust (RPG-2013-106). S.A.K. and A.M. acknowledge support from the German Research Foundation (Deutsche Forschungsgemeinschaft) Major Research Instrumentation Program INST 144/307-1. This is a contribution to IGCP 572, with S.R. sponsored for fieldwork by the Austrian National Committee (Austrian Academy of Sciences) for the International Geoscience Programme (IGCP). We are grateful to R. Newton and A. Thomas for helpful discussions, L. Krystyn for field assistance, F. Maurer for discussions on stratigraphy and providing photomicrographs, and B. Mills for assisting with model studies. Data are available online in the supplementary materials and at www.pangaea.de.